Cardiovascular toxicity after antiangiogenic therapy in persons older than 65 years with advanced renal cell carcinoma. Issue 1 (6th October 2015) - Jang, Sekwon; Zheng, Chaoyi; Tsai, Huei‐Ting; Fu, Alex Z.; Barac, Ana; Atkins, Michael B.; Freedman, Andrew N.; Minasian, Lori; Potosky, Arnold L.
Abstract : BACKGROUND: Sorafenib and sunitinib are oral vascular endothelial growth factor receptor (VEGFR) tyrosine kinase inhibitors (TKIs) approved in 2005 and 2006, respectively, for the treatment of patients with renal cell carcinoma (RCC). A population‐based, observational cohort study of the cardiovascular risk of VEGFR TKI therapy in elderly RCC patients was conducted. METHODS: Using the Surveillance, Epidemiology, and End Results–Medicare database, this study analyzed patients who were 66 years old or older and were diagnosed with RCC from 2000 to 2009. The incidence of cardiovascular adverse events, including congestive heart failure and cardiomyopathy (CHF/CM), acute myocardial infarction (AMI), stroke, and cardiovascular deaths, was examined through December 2010. A Cox proportional hazards model was created to calculate the hazard ratio (HR), and adjustments were made for age, sex, comorbidity, and the use of other systemic therapy. RESULTS: A total of 171 of 670 patients who received sunitinib or sorafenib had cardiovascular events. The incidence rates for CHF/CM, AMI, and stroke were 0.87, 0.14, and 0.14 per 1000 person‐days, respectively. Sunitinib or sorafenib use was associated with an increased risk of cardiovascular events (HR, 1.38; 95% confidence interval [CI], 1.02‐1.87) and especially stroke (HR, 2.84; 95% CI, 1.52‐5.31) in comparison with 788 patients diagnosed with advanced RCC from 2007 to 2009 who were eligible for Part D but did not receive either agent. In subgroup analyses, patients who were 66 to 74 years old at diagnosis had the highest increased risk of stroke associated with the use of either or both drugs. CONCLUSIONS: Sunitinib and sorafenib might be associated with an increased risk of cardiovascular events and particularly stroke. Cancer 2016;122:124–130. © 2015 American Cancer Society . Abstract : Sunitinib and sorafenib are oral vascular endothelial growth factor receptor tyrosine kinase inhibitors approved for the treatment of patients with renal cell carcinoma. Sunitinib and sorafenib are found to be associated with an increased risk of cardiovascular events and particularly stroke.